HUMAN CARE AND MENTAL HEALTH EDUCATION: GENDER INTERSECTIONS - Monique Alves Desidério, Bárbara; Nelson Martins Júnior, Leonidas; Ximenes Oliveira, Silvia; Bento das Chagas, Douglas; Nunes Travassos Peixoto, Claudia; Ferreira de Oliveira, Erivelto; Amâncio Gondim, Bruna (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes the relationships between human care, mental health education, and gender, based on a narrative review of scientific literature published between 2021 and 2024. The investigation focused on understanding how educational practices can contribute to mental health care, especially in contexts marked by social inequalities and marginalized subjectivities. The analysis of the studies resulted in two thematic categories: (1) Popular education and emancipatory care in mental health; and (2) Gender invisibilities and challenges to comprehensive care. The results show that educational practices sensitive to territory, listening, and diversity produce bonds and strengthen the autonomy of subjects experiencing psychological distress. On the other hand, the persistence of biomedical models and the neglect of social markers of difference hinder access to and effectiveness of care. It is concluded that mental health education should be understood as a political and pedagogical process, capable of mobilizing individual and collective transformations, provided it is supported by principles of equity, intersectionality, and social justice.